143 Creation of guidelines for management of patients undergoing abdominal paracentesis for malignant ascites at john eastwood hospice. Issue Volume 8: Issue (2018)Supplement 1 (1st March 2018) - Hill, Stephanie; Wall, Jillian
Abstract : Background: The inpatient unit at John Eastwood Hospice (JEH) is increasingly providing care for patients with malignant ascites, allowing the relief of symptoms via paracentesis. With no established local or national guidelines to follow for peri procedural care, we felt there were varying approaches used for our patients. We set out to create a local protocol for patients undergoing paracentesis, and audit practice against this. Methods: A thorough literature search alongside review of guidelines uploaded to palliativedrugs.com, and those publicly available on the internet, identified eleven established UK guidelines for management of malignant ascites. These were used to construct a protocol for use at JEH. Audit standards were then established alongside this, allowing for retrospective analysis of the management of patients who had undergone paracentesis at JEH. Results: 8 patients had undergone this procedure in the preceding 12 months at JEH, giving a total of 10 completed procedures. Peri procedure management in several areas was variable. A set of baseline observations was documented prior to the procedure in only 10%. Documentation of observations post procedure varied significantly, ranging from half hourly to none at all. 60% had documentation of drain clamping at some point but in none of the cases was there any further detail of the clamping (e.g. length of time). For the 7 drains which were temporary, the length of time they remained in situ ranged from 31 hours to 195 hours. Conclusions: This retrospective audit demonstrates significant variability in the management of patients undergoing paracentesis at JEH, which strayed from that suggested by the newly created guidelines. These guidelines will now be rolled out in the hospice, alongside education to staff, and re-audit completed to ascertain whether there is more uniform practice.